A Skeleton-based Approach to Analyze and Visualize Oculomotor Behavior when Viewing Animated Characters - Thibaut Le Naour; Jean-Pierre Bresciani (Bern Open Publishing, 2017)
Knowing what people look at and understanding how they analyze the dynamic gestures of their peers is an exciting challenge. In this context, we propose a new approach to quantify and visualize the oculomotor behavior of viewers watching the movements of animated characters in dynamic sequences. Using this approach, we were able to illustrate on a 'heat mesh' the gaze distribution of one or several viewers, i.e., the time spent on each part of the body, and to visualize viewers' timelines which are linked to the heat mesh. Our approach notably allows providing an 'intuitive' overview combining the spatial and temporal characteristics of the gaze pattern, and constitutes an efficient tool to quickly compare the oculomotor behaviors of different viewers. The functionalities of our system are illustrated through two use case experiments on 2D and 3D animated media, respectively.